HYPERTENSION FOLLOWING LIVING KIDNEY-DONATION: BETTER SAFE THAN SORRY. A SINGLE-CENTER STUDY. (June 2022) - Mojaat, Malek; Ben Salah, Manel; Salem, Mariem Ben; Handous, Insaf; Hamouda, Mouna; Letaief, Ahmed; Aloui, Sabra; Skhiri, Habib
Abstract : Objective: Evaluate the incidence of hypertension among living kidney-donors. Design and method: This is a retrospective, mono-centric and analytical study. Blood pressure was categorized as per the ACC/AHA hypertension guidelines 2021. Herein, we report the results among 40 living kidney-donors. Results: The study included 40 living kidney donors. The median age was 42 years [34 – 53]s. 75% were female. 62, 5% were married. 80% of donors were related to the recipient. Parents and siblings accounted for 37, 5 % and 35% respectively. 20% were spouses. 3 donors had a family history of CKD. 4 and 6 donors had a family history of hypertension and diabetes respectively. Neither diabetes nor CKD was found among donors' personal history. One donor had a history of hypertension that was well-controlled on monotherapy. Median follow-up was 9 years [6 - 12] with a total period of follow-up ranging from 3 to 32 years. Median systolic and diastolic blood pressures at baseline (SBP, DBP) were 112, 5 and 70 mmHg respectively. During follow-up, we noticed two peaks for the median SBP at six months and three years after nephrectomy reaching a maximal value of 120 mmHg and subsequently decreasing. The comparison with the baseline value did not show a statistically significant difference except at three years (median SBP before nephrectomy:112, 5 mmHg, median SBP at three years after nephrectomy:120 mmHg, p = 0, 03). The median DBP was relatively stable at 70 mmHg during follow-up. However, the comparison with the baseline value has shown a statistically significant elevation compared to baseline starting at two years (p = 0, 002) and remained thereafter. After five years of follow-up, 12.5% and 7.5% of our patients developed stage one and two hypertension respectively. Non-pharmacologic management was enough for stage 1 hypertensive kidney donors but stage 2 patients required pharmacologic agents. Neither cardiovascular complications nor death were encountered during the study period. Conclusions: Our results showed that kidney donation is relatively safe unless a meticulous screening prior to nephrectomy is performed. Regular follow-up allows an early diagnosis of hypertension and prompt initiation of treatment, therefore avoiding severe complications